2021
DOI: 10.1021/acs.chemmater.0c01762
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction and Oxidation of Ruddlesden–Popper-Type La2NiO3F2 within Fluoride-Ion Batteries

Abstract: Within this article, it is shown that an electrochemical defluorination and additional fluorination of Ruddlesden−Poppertype La 2 NiO 3 F 2 is possible within all-solid-state fluoride-ion batteries. Structural changes within the reduced and oxidized phases have been examined by X-ray diffraction studies at different states of charging and discharging. The synthesis of the oxidized phase La 2 NiO 3 F 2+x proved to be successful by structural analysis using both X-ray powder diffraction and automated electron di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 41 publications
(76 reference statements)
1
27
0
Order By: Relevance
“…In a subsequent study Wissel et al reported on topochemical defluorination of La 2 NiO 3 F 2 , leading to the first Ni-containing T′ Ruddlesden–Popper oxyfluoride La 2 NiO 3 F . Additionally, it was found that during the electrochemical oxidation of La 2 NiO 3 F 2 a monoclinic La 2 NiO 3 F 3 is formed. These impressive results demonstrate the wide chemical and structural flexibility of the La 2 Ni­(O,F) 4+ x system.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a subsequent study Wissel et al reported on topochemical defluorination of La 2 NiO 3 F 2 , leading to the first Ni-containing T′ Ruddlesden–Popper oxyfluoride La 2 NiO 3 F . Additionally, it was found that during the electrochemical oxidation of La 2 NiO 3 F 2 a monoclinic La 2 NiO 3 F 3 is formed. These impressive results demonstrate the wide chemical and structural flexibility of the La 2 Ni­(O,F) 4+ x system.…”
Section: Introductionmentioning
confidence: 97%
“…This arrangement leads to a pronounced tilting of the NiO 4 F 2 octahedra accompanied by the formation of alternating narrow and wide channels in the interlayers with the wide channel containing interstitial oxygen ions. In a subsequent study Wissel et al reported on topochemical defluorination of La 2 NiO 3 F 2 , leading to the first Ni-containing T′ Ruddlesden−Popper oxyfluoride La 2 NiO 3 F. 37 Additionally, it was found that during the electrochemical oxidation of La 2 NiO 3 F 2 a monoclinic La 2 NiO 3 F 3 38 is formed. These impressive results demonstrate the wide chemical and structural flexibility of the La 2 Ni(O,F) 4+x system.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Thus, it will be interesting to further explore the synthesis of single-layer T′ nickelates by means of alternative methods also. These include topotactic reactions with different fluorinating/reducing agents and electrochemical methods . In addition, the thin-film route also remains as another possible direction because the Ruddlesden–Popper precursors can be readily obtained in this way (see, e.g., ref ).…”
Section: Discussionmentioning
confidence: 99%
“…These include topotactic reactions with different fluorinating/ reducing agents and electrochemical methods. 33 In addition, the thin-film route also remains as another possible direction because the Ruddlesden−Popper precursors can be readily obtained in this way (see, e.g., ref 34). Thus, our findings are expected to motivate further investigations of these fundamental questions in materials science and condensed matter physics.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…This can be rationalized by assuming that the reaction kinetics at the surface dominate the topotactic fluorination of (La,Sr) 2 NiO 4 thin films. 38 It is known that the total anion content in bulk nickel oxyfluorides with a K 2 NiF 4 -type structure, such as Sr 2 NiO 3 F and La 2 NiO 3 F 2 , varies in the range of 4-5, 17,39,40 where the latter has one additional anion in the rock-salt layer. Sr 2 NiO 3 F consists of [ANi(O,F) 3 ] perovskite and [A(O,F) 1 ] block layers whereas La 2 NiO 3 F 2 is a stacking of [ANi(O,F) 3 ] perovskite and [A(O,F) 2 ] rock-salt layers.…”
Section: Experimental Methodsmentioning
confidence: 99%